Translanguaging and Its Role in English for Critical Thinking Class: Observations at STAHN Mpu Kuturan Singaraja - Pande Eka Putri Pradnyani; Ni Made Ratminingsih; IGA Lokita Purnamika Utami (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
This research is aimed to explore translanguaging practices in tertiary level, specifically in English for Critical Thinking Class at STAHN Mpu Kuturan Singaraja. The goals of this study is to find out the translanguaging types, functions, and language use by the lecturer. The translanguaging practiced by the lecturer were observed through 11 meetings. Observations were conducted to find out how the lecturer practiced translanguaging in the class. With the use of field notes and observation sheets, the data were collected and then presented in the form of table and diagram. The observations were focused on discovering translanguaging frequency, types, functions and languages use. A deductive thematic analysis was employed to analyze the research objectives. This research shows that translanguaging was practiced frequently by the lecturer in terms of pre-activity, main activity, and post-activity. There are 8 (eight) types of translanguaging found along the study that specifically used for specific teaching functions. Moreover, this finding also covers that the lecturer used 3 (three) languages in translanguaging, including English, Indonesian, and Balinese. This study implies that translanguaging as a pedagogical approach plays important roles in multilingal classrooms.